Financial Performance Analysis of PT Total Bangun Persada Tbk for Period 2020–2024 - Fajar Pratama Maulana; Erman Arif Sumirat; Taufik Faturohman (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This research paper examines the 2020 to 2024 financial performance of PT Total Bangun Persada Tbk through an integrated analytical framework. By integrating external environment analysis, industry structure analysis, and internal financial diagnostics, the research aims to measure the sustainability of the performance of the firm. The research utilizes a quantitative case study research design relying on secondary data acquired through audited consolidated financial statements and annual reports. PESTEL analysis and Porter’s Five Forces framework are used to capture macro-environmental and industry-level factors. Internal financial performance is assessed through financial ratio analysis that includes profitability, liquidity, solvency, and activity ratios, and is supplemented by DuPont analysis to determine the structural determinants of return on equity. Moreover, Piotroski F-Score model is used to evaluate how strong are the financial fundamentals of the firm. The findings suggest that PT Total Bangun Persada Tbk has remained resilient in financial performance over the period of observation, despite in a very competitive construction sector. Profitability was consistently positive and enhanced in later years, with sound liquidity management, balanced capital structure, and rising efficiency in operations. Using DuPont analysis, it can be seen that the increase in returns on equity was largely due to operational performance and not leverage. Additionally, the outcomes of 6.40 Piotroski F-Score show moderate-strong financial fundamentals, implying that earnings quality and financial discipline are sustainable. Generally, the results indicate that the financial performance of PT Total Bangun Persada Tbk is healthy and sustainable in the face of tough industry conditions. The research paper contributes to the financial performance literature by incorporation of external environmental analysis and firm-level financial assessment in the Indonesian construction industry.